2022
DOI: 10.1021/acssuschemeng.2c02974
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as a Renewable Substitute for Carbon Black in Lithium-Ion Battery Electrodes

Abstract: Lignin-derived biochar was prepared and characterized toward potential applications as a conductive electrode additive and active lithium host material within lithium-ion batteries (LIBs). This biochar was specifically selected for its high electrical conductivity, which is comparable to that of common conductive carbon black standards (e.g., Super P). Owing to its high electrical conductivity, this biochar serves as an effective conductive additive within electrodes comprising graphite as the active material,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[15][16][17] However, they have not been used as the conductive additives (which are used up to 10% of the electrode composition) due to their inadequate electrical conductivity. Recently, Kane et al 18 reported effective utilization of biochar as a renewable substitute for commercial carbon black due to its higher electrical conductivity for the fabrication of electrodes for Li ion batteries. Biocarbons made from biomass materials can exhibit superior features compared to the carbon black, not only in terms of green and sustainability perspectives but also in terms of their high electrical conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, they have not been used as the conductive additives (which are used up to 10% of the electrode composition) due to their inadequate electrical conductivity. Recently, Kane et al 18 reported effective utilization of biochar as a renewable substitute for commercial carbon black due to its higher electrical conductivity for the fabrication of electrodes for Li ion batteries. Biocarbons made from biomass materials can exhibit superior features compared to the carbon black, not only in terms of green and sustainability perspectives but also in terms of their high electrical conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Recently, conductive biomass carbon with the resistivity of lower than 1 Ω cm possessed the advantages of higher tap density (>0.4 cm 3 g −1 ) than commercialized Super-C45 (0.16 cm 3 g −1 ). [21,22] Their conductivities could be mainly ascribed to surface chemical composition, aggregate structure, porosity, and microcrystalline morphology. [23] Among them, the rearrangement and growth of graphite-like microcrystals would tremendously restrict the rapid movement of 𝜋 electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of biomass, the resulting carbon material may have a different structure, porosity, and composition [17]. An analysis of the literature shows that various types of biomass can be used to prepare biochar for use as a negative electrode material for metal ion batteries: coniferous and broadleaf wood [18,19], lignin [20], herbal plants (for example, bamboo [21] and cotton [22]), starch [23], coconut husks [24,25], banana peel [26,27], rice husks [28,29], grapefruit [30], hairs [31], various aquatic plants, [32] and even leather production waste [33]. The improvement in the electrochemical characteristics of biochar compared to those of graphite is explained by its large specific surface area (100-3000 m 2 g −1 ), making it possible to achieve a specific capacity of 200-800 mAh g −1 after 100 charge/discharge cycles [4,19,22,30,32].…”
Section: Introductionmentioning
confidence: 99%